Assessing changes in subjective and objective function from pre- to post-knee arthroplasty using the Cardiff Dempster–Shafer theory classifier. Issue 4 (11th March 2016) - Worsley, Peter R.; Whatling, Gemma; Barrett, David; Holt, Cathy; Stokes, Maria; Taylor, Mark
Abstract : The purpose of this study is to assess changes in subjective and objective function from pre- to post-knee arthroplasty (KA) using a combined classifier technique. Twenty healthy adults (50–80 years) and 31 KA patients (39–81 years) were studied (4 weeks pre- and 6 months post-KA). Questionnaire measures of subjective pain, joint stability, activity and function were collected. Objective functional assessment included goniometry, ultrasound imaging and 3-D motion analysis/inverse modelling of gait and sit–stand. An optimal set of variables were used to classify function using the Cardiff Dempster–Shafer theory (DST) method. Out of sample accuracy of the classifiers ranged between 90% and 94% for segregating healthy individuals and pre-KA patients. Post-KA subjective function improved with 74% classified as healthy. However, there was minimal improvement in objective measures (23% classified as healthy). The novel use of Cardiff DST segregated KA patients from healthy individuals and estimated changes in function from pre- to post-surgery. KA patients had improved pain and function post-operation but objective knee joint measures remained different to healthy individuals.